Ghouls' rule - Wallace, Karen (London: Catnip Publishing Ltd, 2011)
n this second Creakie Hall story, more visitors come to stay at the haunted hotel. They include Roger and Ritzie Clawback, and Alice and Douglas Milkwarm with their children Bruce and Taffeta
Keywords: Children's stories